Fabrication of manual materials handling mechanism for lifting and feeding of cassava mash - Samuel, T. M.; Aremu, O. O.; Adegbite, S. E.; Onu, L. I.; Olokose, A. A.; Kolawole, O. P. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
Manual materials handling (MMH) devices like jigs and fixtures are required for transporting or positioning materials in large-scale operations. An MMH device was designed to feed cassava mash into fry pan during batch gari-frying. Flow is facilitated through the tapered outlet of a 40 kg-capacity hopper while lifting is achieved by turning a triple-start screwed shaft handle, housed in a u-steel channel framework with wide rigid base that can support holding content in position without buckling. Feeding is done until the content is exhausted ready for reloading. It can deliver more than 160 kg/hr depending on the fry pan capacity and working rate. The worker avoids stretching, bending and twisting the trunk or the neck, or move round more frequently for reloading, thus overcoming the stated ergonomic risk factors and slowness of the work process. The device is also adaptable to other tasks requiring similar feeding mechanism.